Settling For Discrimination: Hiv/Aids Carriers And The Resolution Of Legal Claims - Wilson, Scott (Penerbit Universiti Sains Malaysia (USM Press), 2012)
In the last decade, foundations and international non-governmental organisations (INGOs) have provided financial backing and transferred litigious techniques to Chinese NGOs operating in the HIV/AIDS area. A few NGOs have developed legal programs that provide legal services to HIV/AIDS carriers. HIV/AIDS carriers seek compensation for contracting their disease from transfusions of contaminated blood, illegal and incompetent blood collection as well as discrimination in employment, education and access to medical care. To date, China's courts have accepted few cases brought by HIV/AIDS carriers seeking claims. Many HIV/AIDS carriers have opted to pursue alternative dispute resolution (ADR) such as mediation and conciliation in order to reach a settlement. The settlements offered by ADR, however, institutionalise discriminatory practices. This paper argues that a combination of societal discrimination against HIV/AIDS carriers, government policies and the approach of courts to HIV/AIDS cases strongly discourages litigation and encourages ADR. By analysing court decisions and more importantly, court refusals to hear cases, the article claims that state policies toward HIV/AIDS carriers are driven by state interests more than protecting the rights and interests of HIV/AIDS carriers. The Four Free and One Care (simian yiguanhuai) policy is used by China to channel potential plaintiffs away from litigation. Rather than undermining discrimination, the courts' handling of HIV/AIDS cases helps sustain societal discrimination.